Comparative analysis of hydrazinyl coumarin derivative incorporation in resin-modified and conventional glass ionomer cement - Nor A.F. Azlisham, MSc; Fatimah S.A. Rahman, PhD; Zuliani Mahmood, DClinDent; Dasmawati Mohamad, PhD; Yanti Johari, DClinDent; Ola B. Al-Batayneh, MDSc (Journal of Taibah University Medical Sciences)
الملخص: أهداف البحث: هدفت الدراسة إلى إجراء تحليل مقارن لتأثيرات دمج مشتق الكومارين الهيدرازيني في إسمنت أيونومر الزجاج المعدل بالراتنج والتقليدي على معدلات تحررهما وخصائصهما المضادة للبكتيريا. طرق البحث: استخدم إسمنت أيونومر الزجاج المعدل بالراتنج فوجي الثاني وإسمنت أيونومر الزجاج التقليدي عالي الفلورايد فوجي السابع كمجموعات ضابطة. تم تصنيع مشتق الكومارين الهيدرازيني داخليا، ودمجه في كلا النوعين بنسب وزنية واحد وإثنين بالمئة، وتحليله كيميائيا باستخدام مطيافية الأشعة تحت الحمراء. ثم تم تقييم معدلات تحرر مشتق الكومارين الهيدرازيني والفلورايد باستخدام مطياف الأشعة فوق البنفسجية المرئية ومقياس الفلورايد على التوالي. تم تقييم الخصائص المضادة للبكتيريا ضد المكورات العقدية الدموية باستخدام طريقة الانتشار في الآجار وقياس عكارة النمو البكتيري، متبوعا بملاحظة الشكل البكتيري باستخدام المجهر الإلكتروني الماسح. تم تحليل البيانات إحصائيا باستخدام تحليل التباين أحادي الاتجاه واختبار بونفيروني البعدي. النتائج: أكدت أطياف الأشعة تحت الحمراء وجود مشتق الكومارين الهيدرازيني في مصفوفات الإسمنت. تم تحرر المشتق بنجاح من كلا النوعين بكلتا النسبتين الوزنيتين. لوحظ تحرر أعلى للفلورايد ومناطق تثبيط أكبر مقارنة بالمجموعات الضابطة، مع تأثير أكثر أهمية في النوع المعدل بالراتنج. بالإضافة إلى ذلك، أدى دمج المشتق إلى إبطاء نمو المكورات العقدية الدموية وأظهر تغيرات ملحوظة في شكل البكتيريا خاصة في النوع المعدل بالراتنج. الاستنتاجات: أدى دمج مشتق الكومارين الهيدرازيني في كلا نوعي الإسمنت إلى تحسين تحرر الفلورايد وتعزيز الأنشطة المضادة للبكتيريا، مع ملاحظة تأثير أكثر أهمية في النوع المعدل بالراتنج مقارنة بالنوع التقليدي. Abstract: Objective: The study aimed to conduct a comparative analysis of the effects of incorporating hydrazinyl coumarin derivative (HCD) in resin-modified (RMGIC) and conventional glass ionomer cement (cGIC) on their release profiles and antibacterial properties. Method: Resin-modified GIC, Fuji II LC (F2) and high-fluoride cGIC, Fuji VII (F7) were used as controls. HCD was synthesized in-house, incorporated into both RMGIC and cGICs at 1 % and 2 % weight percentages (w/w), and chemically analyzed using Fourier transform infrared (FTIR) spectroscopy. Then, the F2 containing HCD (GIC-HCD F2) and F7 containing HCD (GIC-HCD F7) were evaluated for HCD and fluoride release profiles using UV Visible spectrophotometer and pH/ISE benchtop fluoridemeter, respectively. The antibacterial properties were assessed against Streptococcus sanguinis using the agar well diffusion method and measurement of bacterial growth turbidity, followed by the observation of the bacterial morphology using scanning electron microscope. The data were statistically analyzed using one-way ANOVA and Bonferroni post-hoc tests. Results: The FTIR spectra confirmed the presence of HCD in the GIC-HCD matrices. HCD was successfully released from both GIC-HCD F2 and GIC-HCD F7 matrices at both weight percentages. Higher fluoride release and inhibitory zones were observed compared to the control groups, with GIC-HCD F2 having a more significant effect than GIC-HCD F7. Additionally, the incorporation of HCD slowed down the growth of Streptococcus sanguinis and showed remarkable changes in bacterial shape specifically on GIC-HCD F2. Conclusion: The incorporation of HCD into both RMGIC and cGIC improved fluoride release and enhanced the antibacterial activities, with a more significant effect observed in RMGIC compared to cGIC.